Programa Bolsa Família: uma avaliação da focalização e dos impactos sobre a pobreza e a desigualdade de renda entre os anos de 2005 e 2015 - Lucena, Camila Queiroz de Aquino (2017)
The Bolsa Família Program (PBF) was institutionalized in 2004, through the unification of the management and execution of income transfer actions of other pre-existing programs in Brazil, constituting the largest care policy in the country. The objective of this study was to evaluate the targeting indicator on the target audience and the impact of the Bolsa Família Program on poverty and income inequality, for the regions of Brazil between the years 2005 and 2015, based on data from the National Household Sample Survey (PNAD). The results suggest over the period studied in Brazil, the focus of PBF was not severely affected. However, in the North and Northeast regions, a large part of the target public of the program is no longer beneficiary therefor affected the targeting indicator, leading it to a small drop. In the other regions, the targeting indicator improved, mainly in the Center-West, which obtained better percentage variation. In addition, the program could obtain better targeting results if the government were able to improve the efficiency of local selection, that is, to include a larger number of households that belong to the target audience of the program, as in the Central-West region. This improvement reflected in the poverty and inequality indicators, with it made it to be the only region making the program increase its impact in the year 2015. For Brazil in general, the impacts on the poverty indicators are minimal, especially in 2015, but reductions are noticed in both years of this study. Although PBF is a useful tool for reducing poverty and inequality, it needs to be improved, either by improving the targeting indicator or by applying sustainable incentives so that families may in future cease receiving the benefit, breaking the perpetuity of the poverty cycle in which they live.